La industria cultural audiovisual en las plataformas de streaming: una muestra de las series de ciencia ficción en Netflix, Amazon Prime Video y Disney+ (Monográficos) - Andrade Mendoza, Karen Indira (2022)
This study has the intention of exposure the transformation that has arisen in the consumption of audiovisual products (especially in the field of film) and of the cultural industry as a result of the growth of the streaming platform market. Television and film production are combined in the same digital environment, with different specifications and applications, adapting to user preferences. Thus, today digital television, the expansion of communication media in digital social networks and streaming platforms tend to cause changes in the ways of approaching the products of the entertainment industry and broaden the growth of the market of the cultural industry. The use and enjoyment of the products of the audiovisual cultural industry of digital platforms and the growth of their presence in our daily lives is permanent, in correspondence with the increased possibilities of accessing a wide production of the film and audiovisual cultural industry. The film production financed and disseminated by these streaming platforms is very diverse and encompasses a great diversity of genres. In this paper, the case of three of these platforms and some of their productions in the field of science fiction will be presented: Netflix, Amazon Prime Video and Disney+, in order to demonstrate the great digital technological advance that these products require, the enormous entertainment potential and futuristic projection of the same, evidencing the current creative capacity.